2001
DOI: 10.1590/s1413-86702001000200006
|View full text |Cite
|
Sign up to set email alerts
|

Successful prevention of HIV transmission from mother to infant in Brazil using a multidisciplinary team approach

Abstract: HIV vertical transmission in Brazil was reduced to a level similar to other countries with the most effective prevention programs using a multidisciplinary team approach. A high level of compliance for use of anti-retroviral drugs, the provision of health education to mothers, and use of formula for all exposed infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0
20

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 27 publications
6
32
0
20
Order By: Relevance
“…Poor education and inaccurate recording of this variable are in agreement with the sociodemographic characteristics of the AIDS epidemic in Brazil 14,16 . The majority of pregnant women included did not have their own source of income or did unskilled work, and this was also observed among HIV-positive pregnant women cared for at a university hospital in the city of Rio de Janeiro 19 . A potential selection bias could occur if women with a higher socioeconomic level do not use public health services, and are therefore not recorded.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Poor education and inaccurate recording of this variable are in agreement with the sociodemographic characteristics of the AIDS epidemic in Brazil 14,16 . The majority of pregnant women included did not have their own source of income or did unskilled work, and this was also observed among HIV-positive pregnant women cared for at a university hospital in the city of Rio de Janeiro 19 . A potential selection bias could occur if women with a higher socioeconomic level do not use public health services, and are therefore not recorded.…”
Section: Discussionmentioning
confidence: 96%
“…After the implementation of the prevention measures by the Brazilian Ministry of Health, the rates of vertical transmission have varied between 2.5% and 8.6% in Brazil 17,18,19,20,21,22,23 . These estimates were obtained predominantly from reference centers in the Southeastern Region, and do not necessarily reflect the existing conditions in the majority of healthcare services.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies have reported low birth weight (LBW) and prematurity to be associated with mother to child transmission, and a possible explanation for the discrepancy could be the higher frequency of LBW and prematurity described in other populations (Nogueira et al 2001, João et al 2003, Magder et al 2005, Szyld et al 2006. However, neonatal diseases such as respiratory distress syndrome, sepsis, and neonatal jaundice were associated with HIV-1 vertical transmission indicating that others factors are associated with the newborn infection.…”
Section: Discussionmentioning
confidence: 97%
“…Estudos têm mostrado que existe uma diminuição do número de casos de transmissão vertical do HIV, principalmente, a partir dos resultados do Protocolo 076 do AIDS Clinical Trials Group (ACTG 076) e do acesso à terapia medicamentosa 3,4,5 . Apesar disso, as taxas de incidência da infecção permanecem elevadas demonstrando a complexidade do problema e das intervenções susceptíveis de resolvê-la, além de que as ações não estão sendo implementadas com a intensidade necessária para reverter a situação 6 .…”
Section: Introductionunclassified